2016
DOI: 10.3171/2015.3.spine13976
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal oblique corridor to the L2–S1 intervertebral discs: an MRI study

Abstract: OBJECT The purpose of this study was to analyze MR images of the lumbar spine and document: 1) the oblique corridor at each lumbar disc level between the psoas muscle and the great vessels, and 2) oblique access to the L5–S1 disc space. Access to the lumbar spine without disruption of the psoas muscle could translate into decreased frequency of postoperative neurological complications observed after a transpsoas approach. The authors investigated the retroperitoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
97
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 40 publications
15
97
2
4
Order By: Relevance
“…2 Even with an adequate corridor, the rate of vascular injury can be up to 10%. 8 The morphology of the sacral slope and iliac crest also needs to be evaluated to ensure that an adequate operative angle can be obtained.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Even with an adequate corridor, the rate of vascular injury can be up to 10%. 8 The morphology of the sacral slope and iliac crest also needs to be evaluated to ensure that an adequate operative angle can be obtained.…”
Section: Figmentioning
confidence: 99%
“…The location of the aorta, vena cava, iliac arteries, and iliac veins can also be evaluated to assess the corridor between the vessels and the spine; this corridor exists in most patients. 8 It is critical to obtain 36-in standing radiographs to preoperatively evaluate not only spinal alignment, but also the position of the iliac crest on the left side to ensure that the procedure can be done (Fig. 3).…”
mentioning
confidence: 99%
“…Two popular and common LLIF procedures are oblique lateral interbody fusion (OLIF) and extreme lateral interbody fusion (XLIF), which each require specially designed instruments [12][13][14][15] . OLIF, especially, enables surgeons to easily and less invasively access the vacant oblique corridor in front of the psoas muscles without causing any splitting, which occurs with XLIF 16,17) . The lateral interbody fusion cage for OLIF has a lordotic angle of 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Cadaveric investigations by Davis et al (28) and Molinares et al (29) demonstrate an adequately sized, left-sided oblique corridor at L2-L5, which could be widened via lateral decubitus positioning and the use of approach retractor systems. The prior study (28) reported left oblique corridor sizes for L2/L3, L3/L4, L4/L5 whilst the latter (29) reported measurements of these levels in addition to L1/L2 and L2/L3. Both studies were consistent in demonstrating that the larger corridors were available in the upper lumbar levels, and has been attributed to the conical morphology of the psoas muscle.…”
Section: Discussionmentioning
confidence: 99%